2015
DOI: 10.1007/s10291-015-0439-3
|View full text |Cite
|
Sign up to set email alerts
|

A cycle slip fixing method with GPS + GLONASS observations in real-time kinematic PPP

Abstract: A key limitation of precise point positioning (PPP) is the long convergence time, which requires about 30 min under normal conditions. Frequent cycle slips or data gaps in real-time operation force repeated re-convergence. Repairing cycle slips with GPS data alone in severely blocked environments is difficult. Adding GLONASS data can supply redundant observations, but adds the difficulty of having to deal with differing wavelengths. We propose a single-difference between epoch (SDBE) method to integrate GPS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…For single epoch GPS satellites, the undifferenced observation equation of dualfrequency code pseudorange and carrier phase can be derived as follows [23][24][25]:…”
Section: Wide-lane Phase Minus Narrow-lane Pseudorange (Wl-nl) Combination With Pseudorange Multipathmentioning
confidence: 99%
See 2 more Smart Citations
“…For single epoch GPS satellites, the undifferenced observation equation of dualfrequency code pseudorange and carrier phase can be derived as follows [23][24][25]:…”
Section: Wide-lane Phase Minus Narrow-lane Pseudorange (Wl-nl) Combination With Pseudorange Multipathmentioning
confidence: 99%
“…Here, the multipath (mp 1 − mp 1 ) and observation noise (ε 1 − ε 2 ) on frequencies L1 and L2 are approximately equal, so the (mp 1 − mp 1 + ε 1 − ε 2 ) term on the right-hand side of the equation can be ignored, and the corresponding GF combination only contains the effects of the ionosphere and the ambiguity. When a cycle slip occurs in the carrier phase observation of the ith epoch, differencing the above equation between adjacent epochs yields the first-order difference GF combination [18,25] containing the ionospheric residual I e−res = (I e (i) − I e (i − 1)) and cycle slip information (λ 2 ∆N 2 − λ 1 ∆N 1 ):…”
Section: Detecting Cycle Slips With Second-order Difference Geometry-free Combination Considering Elevationmentioning
confidence: 99%
See 1 more Smart Citation
“…PPP time and frequency transfer were studied by Zhang and Tu [ 16 ] based on different satellites and precise products, and the results indicated that the PPP time transfer with the precise products from Center for Orbit Determination in Europe (CODE) and GeoForschungsZentrum (GFZ) exhibited better performance than those using other products. In another previous investigation, the precise products from European Space Agency’s Space Operations Centre (ESA/ESOC) were adopted by some researchers for GPS + GLONASS PPP processing [ 19 ]. The precise products from GFZ or WUM were preferred by some other researchers for multi-GNSS PPP processing [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these methods utilizes the time-differenced model. Zhang and Li [14] predicted the atmospheric delays and fixed cycle slip in dual-frequency PPP with a time-differenced model, and Ye et al [15] expanded the method to GPS + Global Navigation Satellite System (GLONASS) observations. Carcanague [16] utilized the time-differenced model to fix cycle slip for single frequency GPS + GLONASS observations.…”
Section: Introductionmentioning
confidence: 99%